2020
DOI: 10.1002/pnp.683
|View full text |Cite
|
Sign up to set email alerts
|

Management of delirium superimposed on dementia in a dementia service

Abstract: Delirium is associated with significant adverse outcomes, including prolonged length of hospital stay, increased dependency and increased mortality but there is a paucity of data pertaining to the management of delirium superimposed on dementia (DSD) in dementia specialist services. Here, the authors discuss their results from measuring the current practice in the management of DSD in a UK dementia specialist unit and an older adult community crisis and home treatment team service and the subsequent action pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Twenty-two primary studies were included in the review, including fourteen quantitative [ 12 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], four qualitative [ 30 , [55] , [56] , [57] ], and four mixed methods studies [ 29 , [58] , [59] , [60] ] ( Table 3 ). The included studies were published between 2003 and 2023 and were conducted in the UK ( n = 7), the USA ( n = 4), Australia ( n = 4), Canada ( n = 3), New Zealand, Finland, Italy, and Germany.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty-two primary studies were included in the review, including fourteen quantitative [ 12 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], four qualitative [ 30 , [55] , [56] , [57] ], and four mixed methods studies [ 29 , [58] , [59] , [60] ] ( Table 3 ). The included studies were published between 2003 and 2023 and were conducted in the UK ( n = 7), the USA ( n = 4), Australia ( n = 4), Canada ( n = 3), New Zealand, Finland, Italy, and Germany.…”
Section: Resultsmentioning
confidence: 99%
“… Lack of interaction Concerns: inadequate information about the data Grealish et al., 2019 [ 56 ]Australia Ethnographic study Delirium Source: seek information initiatively from multiple sources (such as residential facilities, family); Screening tool: not reported Record: delirium screening was not included in the documentation; Report: seek or share information at handover The patients valued being included in care decisions but reported cases where this did not happen. Concerns: none Bakhru et al., 2023 [ 51 ] USA Cross-sectional survey Delirium Source: delirium assessment and management protocol (43% of the ICUs) Tools: CAM ICU (35%) Not reported Not reported Concerns: risk of bias due to 31% non-response rate and social desirability in responses and 18-month survey collection period Chuen et al., 2022 [ 42 ] Canada Case-control study Delirium Source: routine admission assessment; Screening tool: CAM Record and store: patient’s electronic charts; Refer: discharge summary Lack of interaction varied among physicians or medical teams Concerns: none FitzGerald et al., 2020 [ 43 ] UK Descriptive cross-sectional study Delirium superimposed on dementia Not reported Refer: delirium diagnosis disclosed to GP via discharge summary Patients and or families/carers were given information about delirium and its impact Concerns: inadequate information about the data Gilmore-Bykovskyi et al., 2021 [ 44 ]USA Cohort study Dementia Not reported Record and store: clinical notes Refer: written discharge summary (both have high rates of omission) Not reported Co...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations